A Framework for Evaluating the Sustainability of IoT Smart City Projects - Zimmermann, Hans-Dieter (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Although Internet of Things (IoT) technologies are essential for developing sustainable smart cities, systematically evaluating their multidimensional sustainability benefits is a significant challenge. synthesizes existing approaches and proposes a comprehensive, integrated evaluation framework. The proposed framework combines life cycle assessment (LCA) for environmental impacts, cost-benefit analysis (CBA) for economic justification, and multi-criteria decision analysis (MCDA) to integrate stakeholder perspectives and social dimensions. Ultimately, this hybrid approach provides city planners with a rigorous, transparent, and practical tool to ensure that IoT deployments deliver absolute sustainability gains rather than merely relative efficiencies.